Effectiveness of partial splenic embolization in colorectal cancer patients with chemotherapy-induced thrombocytopenia: results of a single institution retrospective study - Li, Dan; Peng, Tao; Wu, Ke-tong; Huang, Yu-ting; Liu, Yang; Wan, Yuan; Zhang, Bo (Frontiers in Oncology, 2024)
ObjectiveTo evaluate the safety and efficacy of partial splenic embolization (PSE) in treating chemotherapy-induced thrombocytopenia (CIT) in patients with colorectal cancer who failed to respond to platelet growth factor therapy.Methods56 patients who underwent PSE were retrospectively analyzed. Based on the inclusion and the exclusion criteria, 29 patients were eligible for the study, of whom one underwent twice PSE procedures due to recurrent thrombocytopenia. The clinical characteristics were retrospectively analyzed with respect to efficacy, safety and outcome.Results60.0% of patients restarted antineoplastic therapy after PSE. There was a positive correlation between difference value of platelet count and embolization material size (Eta Squared = 0.252, p < 0.05). The correlation between the absolute volume of spleen embolized and postoperative complications was analyzed, with a statistically significant result (p < 0.001). The mean preoperative spleen volume, the preoperative platelet count, postoperative platelet count and difference value of platelet count in the non-cirrhotic group were larger than those in the cirrhotic group (p < 0.001). The mean overall survival was 47.7 ± 7.7 months.ConclusionPSE is safe and effective in the treatment of CIT patients with colorectal cancer. The larger the embolized particle, the more platelets grew. The severity of complication was also positively correlated with the absolute volume of spleen embolized. Therefore, large particle embolization materials can be used to improve the efficacy of PSE and reduce complications. For CIT patients with cirrhosis, PSE was less effective in improving platelet count than those without cirrhosis.